2021
DOI: 10.1021/jacsau.1c00352
|View full text |Cite
|
Sign up to set email alerts
|

Toward Glycomaterials with Selectivity as Well as Affinity

Abstract: Multivalent glycosylated materials (polymers, surfaces, and particles) often show high affinity toward carbohydrate binding proteins (e.g., lectins) due to the nonlinear enhancement from the cluster glycoside effect. This affinity gain has potential in applications from diagnostics, biosensors, and targeted delivery to anti-infectives and in an understanding of basic glycobiology. This perspective highlights the question of selectivity, which is less often addressed due to the reductionist nature of glycomater… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 128 publications
0
22
0
Order By: Relevance
“…It is important to note that beyond multivalency/presentation on polymeric scaffolds, glycan arrays have allowed the probing of multi-antennary/branched glycans. 156 The benefits of this approach are well illustrated by Wang et al, who synthesised a series of asymmetrically substituted multiantennary glycans and found differential binding between the structures despite presenting similar terminal sugars. 157…”
Section: Structural and Synthetic Strategies For Glycan Presentationmentioning
confidence: 99%
“…It is important to note that beyond multivalency/presentation on polymeric scaffolds, glycan arrays have allowed the probing of multi-antennary/branched glycans. 156 The benefits of this approach are well illustrated by Wang et al, who synthesised a series of asymmetrically substituted multiantennary glycans and found differential binding between the structures despite presenting similar terminal sugars. 157…”
Section: Structural and Synthetic Strategies For Glycan Presentationmentioning
confidence: 99%
“…100,101 So far, heteroglycopolymers have mainly been studied not only as a way of increasing the strength of binding with soluble lectins but also to enhance the selectivity of the lectin binding process. 101 While these heteroglycopolymers have not yet been used for drug delivery, it was shown that copolymers prepared from two glycomonomers can enhance binding to cells, which is discussed in the next section. 98 ■ GLYCOPOLYMERS FOR TARGETED CELLULAR UPTAKE Valuable lessons were learned when monitoring binding between soluble lectins and glycopolymers of various structures (Figure 6).…”
Section: ■ Lectin Bindingmentioning
confidence: 99%
“…A recent perspective article discussed the possibility of improving affinity of glycomaterials as well as selectivity by modifying the glycan architecture. 101 Careful fine-tuning of structural features can improve selectivity toward specific lectins while binding strength is not jeopardized. While this has not yet been explored in a drug delivery scenario, studies on glycopolymers and soluble lectins confirm that this is an approach worth pursuing.…”
Section: ■ Conclusion and Outlookmentioning
confidence: 99%
“…[ 19 ] Several complications obstruct the study of native mucins and our ability to exploit their properties for biomedical or engineering applications, thus motivating the synthesis of mucin analogs or mucin‐mimic polymers. [ 20,21 ] Mucin needs to be harvested while ensuring its function away from epithelium. Furthermore, native mucins suffer from variable glycosylation causing high batch‐to‐batch variability.…”
Section: Introductionmentioning
confidence: 99%